2021
DOI: 10.3389/fimmu.2021.797432
|View full text |Cite|
|
Sign up to set email alerts
|

Efficient In Vitro Generation of IL-22-Secreting ILC3 From CD34+ Hematopoietic Progenitors in a Human Mesenchymal Stem Cell Niche

Abstract: Innate lymphoid cells (ILCs) and in particular ILC3s have been described to be vital for mucosal barrier functions and homeostasis within the gastrointestinal (GI) tract. Importantly, IL-22-secreting ILC3 have been implicated in the control of inflammatory bowel disease (IBD) and were shown to reduce the incidence of graft-versus-host disease (GvHD) as well as the risk of transplant rejection. Unfortunately, IL-22-secreting ILC3 are primarily located in mucosal tissues and are not found within the circulation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 70 publications
(113 reference statements)
0
3
0
Order By: Relevance
“…In-vitro culture of enriched human ILC3 is a prolonged process that requires several growth factors (SCF, IL-7, Flt-3L, IL-2, IL-15). The success of ILC3 propagation in vitro can depend upon a layer of cells to support ILC3 proliferation (such as mesenchymal stem cells) ( 79 ). Mouse-enriched ILC3s are usually cultured with SCF and IL-7 and on occasion with the addition of IL-1β, IL-12, or IL-23.…”
Section: Ilc3 Sorting and Culturementioning
confidence: 99%
See 1 more Smart Citation
“…In-vitro culture of enriched human ILC3 is a prolonged process that requires several growth factors (SCF, IL-7, Flt-3L, IL-2, IL-15). The success of ILC3 propagation in vitro can depend upon a layer of cells to support ILC3 proliferation (such as mesenchymal stem cells) ( 79 ). Mouse-enriched ILC3s are usually cultured with SCF and IL-7 and on occasion with the addition of IL-1β, IL-12, or IL-23.…”
Section: Ilc3 Sorting and Culturementioning
confidence: 99%
“…Having in mind the required precision in ILC3 phenotyping, sorting, and culture conditions and the paucity of tissue ILC3, as well as the limited availability of organs/tissues for their isolation, the use of ILC3 for human cell therapy seems to be complex and unrealistic. Still, alternative strategies, such as propagating tissue-like ILC3 from CD34 + hematopoietic progenitors ( 79 ), could overcome the above-stated obstacles on the road toward ILC3-based therapy.…”
Section: Ilc3 Sorting and Culturementioning
confidence: 99%
“…Umbilical cord blood (CB) is another home of immune and hematopoietic cells of basic and applied interest. It not only is a source for allogeneic stem cells used for transplantation, but also holds great promise as a source for cell-based tumor therapy and the in vitro generation of immune cells with therapeutic potential that are rare in peripheral blood such as innate lymphoid cells (ILCs) and plasmacytoid dendritic cells (8)(9)(10)(11). Here, Greppi et al have identified a novel subpopulation of NK cells in CB that express the checkpoint inhibitor programmed death receptor 1 (PD1).…”
mentioning
confidence: 99%